Peran Pesantren Sebagai Pusat Konseling Pernikahan Islami Dalam Mewujudkan Keluarga Sakinah Di Jombang - Rahmawati, Eka; Amriana (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2025)
Marriage in Islam aims to form a harmonious, loving, and compassionate family. However, the increasing divorce rate in Indonesia, including in Jombang, demonstrates the need for efforts to strengthen family resilience through a spiritual approach. Islamic boarding schools, as traditional Islamic educational institutions, play a crucial role in providing marriage guidance and counseling based on Islamic values. This study aims to analyze the role of Islamic boarding schools in Jombang as centers for Islamic marriage counseling in realizing a harmonious family. The research method used is descriptive qualitative with a library research approach, through analysis of various scientific literature and secondary data sources related to Islamic counseling guidance and the social role of Islamic boarding schools. The results show that Islamic boarding schools have three main functions in marriage counseling: preventive (premarital guidance), curative (resolving domestic conflicts), and educational (continuous family guidance). These three functions strengthen the role of Islamic boarding schools as institutions for moral and spiritual development in the community. In conclusion, Islamic boarding schools play a strategic role in helping married couples build harmonious families based on Islamic values, as well as being effective counseling centers in realizing a harmonious family in Jombang.